2014
DOI: 10.1109/tgrs.2013.2238241
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Infrared Multipath Reflection from Breaking Waves Observed at Large Incidence Angles

Abstract: The infrared signature of breaking waves at large incidence angles was investigated using laboratory experiments and a radiometric model. Infrared imagery of the water surface at incidence angles greater than 70 • shows multipath reflections for both spilling and plunging waves generated using a programmable wave maker. For the spilling breakers, the multipath signature was initially distinct from the breaking wave front roller signature but then merged to create a single large bright distributed target. For t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Recent work with IR imagers operating in the mid-and longwave spectral regions has revealed a complex signature of residual foam due to breaking waves. Although limited data are available, they show that the foam IR brightness temperature of actively breaking waves is higher than a quiescent water surface at the same physical temperature [23,24]. Furthermore, this increase in brightness temperature is due to a one to three percent increase in the emissivity for typical oblique viewing angles [13,25].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work with IR imagers operating in the mid-and longwave spectral regions has revealed a complex signature of residual foam due to breaking waves. Although limited data are available, they show that the foam IR brightness temperature of actively breaking waves is higher than a quiescent water surface at the same physical temperature [23,24]. Furthermore, this increase in brightness temperature is due to a one to three percent increase in the emissivity for typical oblique viewing angles [13,25].…”
Section: Introductionmentioning
confidence: 99%
“…This effect has been shown by Niclos et al [2007] to hold whether the sea surface is considered a diffuse or specular reflector. Newer data have extended this relationship to 858 incidence angle [Branch et al, 2012], and the resulting emissivity curves were found in agreement with those from Niclos et al [2007]. The higher emissivity of foam causes foam produced by an actively breaking wave to have a higher apparent temperature than the undisturbed sea surface.…”
Section: Thermal Signal Of the Sea Surfacementioning
confidence: 55%
“…In this study, the emphasis is on remotely sensed SST as a prerequisite parameter to estimating accurate ocean/sea subsurface water temperature. In the remote sensing approaches used to determine SST, water emissivity is an important constant in the SST equation [103]. When there is a slight spatial change in thermal inertia and the structure of the water, the emissivity is equal both vertically and horizontally, and is assumed to be 1 or near 1.…”
Section: Accurate Sea Surface Temperaturementioning
confidence: 99%